Physical Characteristics and Water Content of Sea lettuce (Ulva lactuca) - Anindinda Prameswari Hastiza; Edison Edison; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTSea lettuce is a type of green algae which is included in the father seaweed, namely edible seaweed, which contains antioxidants, antibacterial, antifungal and anti-tumor properties. This study aims to determine the characteristics and water content in sea lettuce. The material and methods in this study were secondary data and literature studies, analyzed descriptively by describing the c haracteristics and water content of sea lettuce. The result shown that sea lettue had physical characteristics with thallus which resembles a thin sheet, the edges of thallus are wavy and smooth, have a bright green to dark green color. Moisture content of sea lettuce has an average content 89.30%. Keyword: Sea lettuce, characteristics, water content 1) Student of the Faculty of Fisheries and Maritime Science, University of Riau2) Lecturers of the Faculty of Fisheries and Maritime Science, University of Riau